Pengaruh Pemberian Suplemen Selenium dan Iodium terhadap Status Gizi, Skor IQ dan Jumlah Tanda Khas Kretin pada Anak Sekolah Dasar - Hanim, Diffah; Rimbawan, Rimbawan; Khomsan, Ali; Martianto, Drajat (Jurnal Kedokteran YARSI, 2008)
Iodine Deficiency Disorder (IDD) and Protein Energy Malnutrition (PEM) is still a public health problem in school-aged children living in endemic area. This study was aimed to investigate some biochemical parameters, nutritional status and IQ score in children in endemic area of Boyolali Regency, Central Java. Before and after quasi experimental study design was implemented. A number of 115 school-aged children (9-12 years) with iodine deficiency, PEM problem and attributed to 6-10 sign of cretinism were selected as study sample. Sampling was conducted by using random sampling procedure. The Group of treatment were selenium supplement (n=34), iodine supplement (n=35), selenium and iodine (n=18) and placebo (n=28). The study found that selenium, iodine, selenium and iodine supplement intervention were significantly reduce the stunted (p=0.04, r=0.587) and underweight (p=0.01, r=0.87). Selenium and iodine were able to improved IQ score of those who were deficient with IQ score under 20 (14.8% student) to IQ score 20-35. The children with very severe deficiency of iodine and selenium (17.4%) and IQ score under 20 could be corrected by iodine supplement and IQ score increased to 20-35. A reduction of the cretinism attributes were found among the children after intervention (from 6-11 sign to 5-10 sign). Anomaly of erythrocytes and leucocytes were found to be associated with severity of stunted and underweight, number of attributes and deficiency level of selenium and iodine.